2007
DOI: 10.1002/ajh.20993
|View full text |Cite
|
Sign up to set email alerts
|

GATA‐1 transcription factor is up‐regulated in bone marrow hematopoietic progenitor CD34+ and erythroid CD71+ cells in myelodysplastic syndromes

Abstract: GATA-1 is a transcription factor governing the production of erythroid and megakaryocytic cells. Unobstructed GATA-1 expression in early progenitor cells commits them to the myeloid lineage, channeling its differentiation towards erythrocytes and megakaryocytes. Myelodysplastic Syndromes (MDS) are clonal disorders of the hematopoietic stem cell frequently presenting dysplasia in erythroid and/or megakaryocytic lineage. We reasoned that measurement of GATA-1 expression levels in hematopoietic progenitor CD34 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
3
4
0
1
Order By: Relevance
“…Increased apoptotic death of CD34 ϩ hematopoietic progenitors has been assumed to be one of the mechanisms underlying the hematopoietic defect in early-stage MDS patients (39). One clinical report found that GATA1 mRNA expression had increased approximately 10-fold in the CD34 ϩ progenitors of MDS patients (40). In this study, we found that ectopic increases of GATA1 expression in HSCs led them to apoptosis and subsequent depletion.…”
Section: Discussionsupporting
confidence: 54%
“…Increased apoptotic death of CD34 ϩ hematopoietic progenitors has been assumed to be one of the mechanisms underlying the hematopoietic defect in early-stage MDS patients (39). One clinical report found that GATA1 mRNA expression had increased approximately 10-fold in the CD34 ϩ progenitors of MDS patients (40). In this study, we found that ectopic increases of GATA1 expression in HSCs led them to apoptosis and subsequent depletion.…”
Section: Discussionsupporting
confidence: 54%
“…In our results, increase of GATA-1 mRNA was observed from stem cell fraction to progenitor cell fraction. Furthermore, Maratheftis et al 33 reported the upregulation of GATA-1 mRNA of CD34 þ cells in myelodysplastic syndrome compared with that of normal control.…”
Section: Gata-mentioning
confidence: 99%
“…While GATA1 is as an important transcriptional regulator in normal erythropoiesis [36], BCL-xl is implicated in the anti-apoptosis effect of EPO on erythroblasts [37]. Aberrant GATA1 expression in MDS have been described with evidence of increased GATA1 expression in bone marrow CD34+ stem and progenitor cells as well as CD71+ erythroblasts from MDS patients [38]. Furthermore, normal upregulation of GATA1 and BCL-xl during human erythroid differentiation is lost in MDS [39].…”
Section: Normalized Expression Of Epo Downstream Genes In Bone Marrow...mentioning
confidence: 99%